HEAT simulation and IR data comparison for ST40 plasma-facing components - E.J.C. Tinacba; T.K. Gray; M. Moscheni; C. Marsden; E. Vekshina; O. Asunta; P. Bunting; S. McNamara; A. Rengle; T. Looby; E.A. Unterberg (Nuclear Materials and Energy)
The Heat Flux Engineering Analysis Toolkit (HEAT) (Looby et al., 2022) was used to simulate the heat flux, qtarget, on ST40 molybdenum divertors. Results were compared with experimental infrared (IR) data. Two shots, 11419 and 11376 at time instants 119 ms and 120 ms, with lower-biased disconnected double null geometries, were studied. Single-λ and multi-λ heat flux profiles were used as input in HEAT simulation. The simulated qtarget was used in OpenFOAM to calculate the corresponding temperature, T, on the divertors. Results showed that a good agreement on the simulated qtarget, T and shape of the heat flux on the divertor with the IR data was achieved when a multi-λ heat flux profile was used for 11419, and single-λ heat flux profile for 11376. This indicates that HEAT can be reliable in analyzing and understanding the heat loading of plasma facing components in tokamak devices.